Regional anesthetics: traditions and innovations - Haas, A. I.; Koval, D. O.; Haas, O. O. (Pain medicine, 2018)
The wide implementation of different regional anesthesia techniques is also actual in pediatric anesthesiology. Using modern methods of regional anesthesia (RA) and modern local anesthetics is a new level in development of pediatric anesthesiology. This article is about advantages of regional pediatric anesthesia in intra- and post-surgery pain management and analgesia. We analyse the techniques of spinal and epidural anesthesia, as well as their varieties such as unipolar spinal block and caudal anesthesia, compare their advantages and disadvantages. Some more techniques such as paravertebral block, TAP-block are considered as an alternative to epidural anesthesia. Methods and possibilities of ilioinguinal, iliohypogastric and TAP-blocks are also mentioned here. The use of the above-mentioned methods allows to reduce the use of narcotic analgesics and hypnotics and, as a consequence, reduces their systemic effects on the child’s body. These methods are safer for use, since they allow you to plan a safe anesthetic for each child and minimize complications.